'Watch this space': the cavum septum pellucidum during development. (7th June 2011) - Kyriakopoulou, V; Gray, L; Allsop, J M; McGuinness, A K; Ederies, A; Rutherford, M A
Abstract : Background: The cavum septum pellucidum (CSP) is a CSF-filled structure located in the centre of the fetal brain and is considered a biomarker of atypical brain development when enlarged or absent. While patent during fetal life, its presence in adulthood is uncommon and has been associated with various psychiatric disorders. Although routinely imaged in fetal and neonatal scans, its formation, size and evolution in normal and abnormal clinical situations has not been systematically studied. The aim of this study was to characterise the morphology and development of the CSP using MRI in normal fetuses from 23 to 38 weeks of gestation. This is the first MRI study to investigate the development of the fetal CSP. Methods: This study was ethically approved, and informed written consent was obtained from all participants. 36 healthy volunteers (gestation range, 23–38 weeks) were recruited for a fetal MR scan performed in a 1.5T scanner. T2-weighted dynamic images of the fetal brain were acquired and reconstructed into a 3D brain. The maximum width and the volume of the CSP were measured in all fetal brains and plotted against gestational age. Changes in shape through gestation were visually assessed. Results/Conclusion: CSP width and volume showed an increase from 23 weeks of gestation, peaking at 30 weeks and decreasing thereafter. There was a positive but non-linear correlation between the width and the volume suggesting that CSP closure occurs not only due to closure of the two parallel septal leaves but is possibly influenced by the development of the surrounding structures.